KESEHATAN RUMAH DI WILAYAH KERJA PUSKESMAS I KARANGASEM BALI 2015 - Wijaya, I Gusti Putu Sinar Adinata; Dewi, Wayan Citra Wulan Sucipta (E-Jurnal Medika Udayana, 2016)
DESCRIPTION OF HEALTHY HOUSE IN PUBLIC HEALTH CENTER I KARANGASEM BALI 2015 ABSTRACT Poverty caused inability of the individual to fulfill their requirements of proper residential based from the aspect of healthiness. Healthy houses were a shelter, dwelling, also as a media for family building with the result that all of the member could be productive. Unhealthy houses might increase the risk for the family member to be subjected to all kind of diseases. The purpose of this study was to understand the descriptive of healthy houses in the work area of Karangasem I public health center. The cross-sectional-descriptive study was done in the Pertima and Bugbug Village as the representative of the work area. Eighty-one houses chosen as samples of study from both of the village with the proportional to size random sampling method. The data collected through the interview to obtain the characteristics and unmated daily habit of respondents and also to observe the houses component and sanitation facility. The result of the study showed that only 38,3% of houses that fulfilled the healthy houses criteria. Based on the components of the house, all of them (100%) had windows in the living room, most of them had windows in the bed room (96,3%), tiled floor (97,5%), brick wall (91,4%), clean and safe ceiling (67,9%), and also permanent ventilation with the size of more than 10% of the floor size (58%). Houses with the kitchen ventilation more than 10% of the floor size was only 49,4% and the houses with the good lighting was only 30,9%. Based on sanitation facility, all of them (100%) had private clean water facility and most of them (91,4%) had toilet that connected to the septic tank. Houses with the sewage wastewater disposal facility were only 24,7% and houses that had the waterproof and closed trash were only 2,5%. Based on the family habit, all of them (100%) defecated using the water closet. Most of them cleaned the yard (97,5%), opened the window in living room (88,9%) and bedroom (70,5%) everyday. The habit for throwing the trash daily was 39,5%.
Keywords: Healthy house, house components, sanitary facility, unmate daily habit